2017
DOI: 10.1136/bmjopen-2016-011742
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a step counter during treadmill and daily life walking by healthy adults and patients with cardiac disease

Abstract: BackgroundStep counters have been used to observe activity and support physical activity, but there is limited evidence on their accuracy.ObjectiveThe purpose was to investigate the step accuracy of the Fitbit Zip (Zip) in healthy adults during treadmill walking and in patients with cardiac disease while hospitalised at home.MethodsTwenty healthy adults aged 39±13.79 (mean ±SD) wore four Zips while walking on a treadmill at different speeds (1.7–6.1 km/hour), and 24 patients with cardiac disease (age 67±10.03)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 47 publications
1
61
1
Order By: Relevance
“…For the hip-worn PAMs among all participants and for wrist-worn PAMs among participants without rollators, the relationship was similar. In line with several other studies of consumer-grade PAMs in older adults, we found a higher accuracy in faster walking older adults [17,19,20,24]. As described in the introduction, walkers with assistive devices are more likely to have alternative gait pattern compared to walkers using no assistive device.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For the hip-worn PAMs among all participants and for wrist-worn PAMs among participants without rollators, the relationship was similar. In line with several other studies of consumer-grade PAMs in older adults, we found a higher accuracy in faster walking older adults [17,19,20,24]. As described in the introduction, walkers with assistive devices are more likely to have alternative gait pattern compared to walkers using no assistive device.…”
Section: Discussionsupporting
confidence: 92%
“…In this model, each tester measures each participant, and testers are considered representative of a larger population of testers. Previously studies have either used Pearson correlation coefficients [19], unspecified ICC [17,18] or ICC (2,1) [12,14,15]. Agreement between two continuous outcomes should be reported using ICC values [25], and future studies should as a minimum report the specific sub-type of ICC as well as difference (percentage or mean) allowing the results to be compared between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pedometers are less accurate when the sensor is attached to the wrist or hip, compared to ankle-based pedometers. Similarly, slower walking speed, unsteady and uneven gaits influence accuracy [33][34][35][36]. In the case of accelerometers, Nelson et al [6] found that wrist-worn accelerometers are more accurate than hip-worn sensors.…”
Section: The Tracker and Sensor Typesmentioning
confidence: 99%
“…The bracelet in the study (see the Table of Materials) was chosen as it is commonly used in various studies 22,23 . Also, for a population with reduced functional capacity, it is better and more suitable as it is more sensitive to movement 24 . As for the sample frequency, the pulse samples are taken continuously during activity and every minute during the day.…”
Section: Introductionmentioning
confidence: 99%